Fabrication of New Cellulose-Based Sorbents for Fast and Efficient Removal of Hazardous Al(III) Ions from Their Aqueous Solutions. Issue 4 (2nd April 2016) - Yousif, Ahmed M.; Labib, Sherif A.
Abstract : Cellulose was used as a base polymer in two prepared resins when it was grafted by glycidyl methacrylate (GMA) then immobilized with 8-hydroxyquinoline by two different procedures. The resulting resins were characterized by infrared (IR) spectroscopy, thermogravimetric analysis (TGA), and nitrogen surface area measurements (BET). The two resins were used in the removal of hazardous Al(III) from their aqueous solutions. The present work discussed the preparation and the effect of spacer arms length used in the functionalization steps on the adsorption process. The resin with longer spacer arm showed faster kinetics compared with the other one toward Al(III) ion adsorption. Fast and efficient adsorption of hazardous Al(III) ions from drinking water by these resins indicates their applicability in water treatment applied field. Thermodynamic parameters were calculated for the studied resins and showed that they possess spontaneous exothermic nature. The regeneration efficiencies reached 90 ± 0.5% over three cycles using a mixture of 2 M HCl and 0.5 M HNO3 . GRAPHICAL ABSTRACT: